Steel plate contribution to load-carrying capacity of retrofitted RC beams - Arslan, G.; Sevuk, F.; Ekiz, I. (ELSEVIER SCI LTD, 2008)
Experiments for flexural strengthening of rectangular reinforced concrete (RC) beams using epoxy-bonded continuous horizontal steel plates have been carried out. Seven reference beams have been loaded monotonically up to maximum load capacities in order to define load-deflection relationship of damaged beams. The beams have been then repaired and strengthened using different steel plate configurations as defined by variations in plate curtailment length. These retrofitted RC beams have been then tested in the same conditions as reference beams and the contribution of the repairing and strengthening techniques on load-carrying capacity have been investigated. The experimental programme is supported by a three-dimensional nonlinear finite element analysis and an equation for ultimate shear capacity of retrofitted beams is proposed except for beams which have steel plate extended to the supports and/or additional anchorages at the ends of steel plate. At the end of experiments and finite element analyses, it is concluded that the investigated repairing and strengthening technique is highly effective on improving the flexural behavior of previously damaged slender RC beams. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: flexural strengthening; reinforced concrete; epoxy-bonded steel plate; nonlinear finite element analysis; retrofitted beams; load-carrying capacity; REINFORCED-CONCRETE BEAMS; INTERFACIAL STRESSES; FINITE-ELEMENT; Construction & Building Technology; Engineering; Materials Science